Effect of Non-Performing Financing and Operating Expenses of Operating Income on Profitability of Islamic Commercial Banks - Awaluddin, Muhammad (ADPEBI, 2022)
This study aims to determine the effect of Non-Performing Financing and Operating Expenses on Operating Income on the Profitability of Islamic Commercial Banks in Indonesia. This type of research uses quantitative research. The population used in this study were all Islamic Commercial Banks in Indonesia registered with the Financial Services Authority from 2016 - 2020, which amounted to 14 Islamic Commercial Banks. The sampling technique in this study used a purposive sampling method with a sample of six banks, namely Bank Muamalat Indonesia, Bank Mandiri Syariah, BNI Syariah, BRI Syariah, Bank Bukopin Syariah, and BCA Syariah. The data collection method used in this research is a library study in the form of document searches related to all aspects studied. And this study uses the Classical Assumption Test, Multiple Linear Regression, and Hypothesis Testing